Electrochemical behaviour of dissolved proton species in room temperature ionic liquids. - Silvester, Debbie; Compton, R. (N/A, 2009)
Understanding the nature of dissolved species in ionic liquids is important, particularlywhen using them as reaction media to replace volatile organic solvents. Electrochemicaltechniques such as cyclic voltammetry and potential-step chronoamperometry are verypowerful tools used to study electrochemical reactions, elucidate mechanisms andquantify diffusion parameters. These techniques have been used in various studies on thebehaviour of dissolved species in ionic liquids. Particularly, the behaviour of hydrogen or?protic? species in ionic liquids can give some insight into the hydrogen bondingcharacteristics of the ionic liquids (individual cation/anion combination) and eventuallythe pH properties of the solvents. We have looked 1,2 at the direct oxidation of hydrogengas in ten ionic liquids with various cation/anion combinations. The mechanism involvesthe two-electron oxidation of hydrogen to the electrogenerated proton, which is thoughtto then combine with the anion (A-) of the ionic liquid. The appearance and position ofthe reverse (reduction) peak on the voltammogram is thought to depend on three factors:(1) the stability of the solvated proton, HA, (2) the position of equilibrium of theprotonation reaction HA = H+ + A-, and (3) any follow-up chemistry e.g. dissociation orreaction of the solvated proton, HA. This is discussed for all ten ionic liquids studied.Solubilities of hydrogen gas are found to be in the range ca. 3-10 mM and diffusioncoefficients are calculated to be of the order 10-10 m2 s-1, with no evidence that the Stokes-Einstein law applies for the diffusion of hydrogen gas in ionic liquids.